Los movimientos guerrilleros en Colombia (1948-1990): la cultura política convencional y la desproporcionalidad de la violencia (2020)
The potential of political violence and the specific forms of its manifestations in Colombia can only be adequately explained if the dimension of the culture of authoritarianism and its pre-modern characteristics are included in the analysis. The causes of political violence can be described as multiple: the destruction of the traditional social fabric, demographic pressure, large internal migrations, expectations of individual progress, weak institutions and incomplete democratization. The guerrilla movements took advantage of these factors, but were unable to provide the population with a modern, realistic and credible alternative. Guerrilla movements in Colombia (1948-1990): conventional political culture and the disproportionality of violence.